Two hydrazones derived from 1‐aryl‐3‐(p‐substituted phenyl)prop‐2‐en‐1‐one: synthesis, crystal structure, Hirshfeld surface analysis and in vitro biological properties. Issue 6 (23rd May 2018) - Dammene Debbih, Ouafa; Sid, Assia; Bouchene, Rafika; Bouacida, Sofiane; Mazouz, Wissam; Gherraf, Noureddine
Abstract : Two hydrazones exhibit zigzag chains interconnected through noncovalent contacts. A quantitative analysis of the intermolecular interactions in the crystal structures was performed. The results of antibacterial and antioxidant activity evaluation indicated that the compounds show significant activity against Gram negative Escherichia coli strain. Abstract : Two chalcones were synthesized by the aldolic condensation of enolizable aromatic ketones with substituted benzaldehydes under Claisen–Schmidt reaction conditions and then treated with 2, 4‐dinitrophenylhydrazine to yield their corresponding hydrazones. The two ( E, Z )‐2, 4‐dinitrophenylhydrazone structures, namely ( Z )‐1‐(2, 4‐dinitrophenyl)‐2‐[( E )‐3‐(4‐methylphenyl)‐1‐phenylallylidene]hydrazine, C22 H18 N4 O4, (H1 ), and ( Z )‐1‐[( E )‐3‐(4‐chlorophenyl)‐1‐(naphthalen‐1‐yl)allylidene]‐2‐(2, 4‐dinitrophenyl)hydrazine, C25 H17 ClN4 O4, (H2 ), were isolated by recrystallization and characterized by FT–IR, UV–Vis, single‐crystal and powder X‐ray diffraction methods. The UV–Vis spectra of the hydrazones have been studied in two organic solvents of different polarity. It was found that (H2 ) has a molar extinction coefficient larger than 40000. Single‐crystal X‐ray diffraction analysis reveals that the molecular zigzag chains of (H1 ) and (H2 ) are interconnected through noncovalent contacts. A quantitative analysis of the intermolecular interactions in the crystal structures has been performed using Hirshfeld surface analysis. All the synthesized chalcones and hydrazones were evaluated for their antibacterial and antioxidant activities. Results indicate that the studied compounds show significant activity against Gram negative Escherichia coli strain and the chalcone 3‐(4‐methylphenyl)‐1‐phenylprop‐2‐en‐1‐one, (C1 ), was the most effective. In addition, only hydrazone (H1 ) displayed a moderate DPPH (2, 2‐diphenyl‐1‐picryl hydrazyl) scavenging efficiency.